GPs’ understanding and practice of safety netting for potential cancer presentations: a qualitative study in primary care - Evans, J; Ziebland, S; MacArtney, JI; Bankhead, CR; Rose, PW; Nicholson, BD (Royal College of General Practitioners, 2018)
Background: Safety Netting is a diagnostic strategy used in UK primary care to ensure patients are monitored until their symptoms or signs are explained. Despite being recommended in cancer diagnosis guidelines, little evidence exists about which components are effective in modern-day primary care. Aim: We aimed to understand the reality of safety netting for cancer in contemporary primary care. Design and Setting: A qualitative study of GPs in Oxfordshire. Method: In-depth interviews with a purposive sample of 25 qualified GPs. Interviews were recorded and transcribed verbatim and analysed thematically using constant comparison. Results: GPs revealed uncertainty about which aspects of clinical practice are considered safety netting. They use bespoke personal strategies, often developed from past mistakes, without knowledge of their colleagues practice. Safety netting varies according to the perceived risk of cancer, the perceived reliability of each patient to follow advice, GP working patterns and time pressures. Increasing workload, short appointments, and a reluctance to over-burden hospital systems or create unnecessary patient anxiety, have together led to a strategy of selective active follow-up of patients perceived to be at higher risk of cancer or less able to act autonomously. This leaves patients with low-risk-but-not-no-risk symptoms of cancer with less robust or absent safety netting. Conclusions: GPs would benefit from clearer guidance on which aspects of clinical practice contribute to effective safety netting (for cancer). Practice systems that enable active follow-up of patients with low-risk but-not-no-risk symptoms that could represent malignancy could reduce delays in cancer diagnosis without increasing GP workload.